Efektivitas Trichoderma atroviride dalam Pengendalian Penyakit dan Peningkatan Pertumbuhan Bibit Cengkeh - Istiqomah, Dina; Rahayuniati, Ruth Feti (Jurnal Agro Wiralodra, 2025)
Clove production in Indonesia is frequently encounters significant impediments from pathogenic diseases during the crucial nursery stage. Reliance on chemical fungicides raises environmental concerns and contributes to pathogen resistance. This study aimed to evaluate the effectiveness of Trichoderma atroviride as a biocontrol agent for disease management and growth promotion in clove seedlings. This research was conducted using a non-factorial Completely Randomized Design with 6 replications. The method involved applying T. atroviride at varying dosages to clove seedlings, followed by observations of disease intensity and growth parameters such as plant height and stem diameter. The results demonstrated that T. atroviride application significantly reduced disease intensity, with an optimal dosage of 10 ml/plant exhibiting very high effectiveness. Morover, T. atroviride consistently led to significant increases in seedling height and stem diameter, resulting in more robust and physiologically well-developed planting material suitable for transplantation.